Nucleoside analogue activators of cyclic AMP-independent protein kinase A of Trypanosoma - Sabine Bachmaier (Nature Portfolio, 2019)
Protein kinase A (PKA) is typically activated by cAMP. Here, Bachmaier et al. show that PKA of Trypanosoma is activated by nucleoside-related ligands, explain the ligand selectivity swap by a co-crystal structure of trypanosome PKAR, and identify potential downstream targets by phosphoproteomics.